Pemurnian Parsial dan Karakterisasi Kitinase Asal Jamur Entomopatogen Beauveria bassiana Isolat BB200109 - Yadi Suryadi; Tri P. Priyatno; I Made Samudra; Dwi N. Susilowati; Nuni Lawati; Eman Kustaman (Jurnal AgroBiogen, 2013)
Beauveria bassiana is one of theentomopathogenic fungus that produces chitinase wheninfecting its host. This study was aimed to purify, isolate andcharacterize chitinase of B. bassiana isolate BB200109.Pathogen identity was determined both morphologically andmolecularly using ITS primer, whilst characterization wasdone at various conditions i.e. temperature, pH, metal ionand incubation time. Results showed that the BB200109isolate belonged to B. bassiana. The isolate producedextracellular chitinase with chitinolytic index of 1.035. Partialpurification of three saturated ammonium sulphateprecipitation (10, 30, and 70%) showed maximum purity of1.2 times, while dialysis could increase the purity of 1.9times compared to that of crude enzyme extract.Characterization results showed that the chitinase isolatedfrom B. bassiana isolate BB200109 had an optimum activityat pH 4, temperature 50oC, and optimum incubation time of90 minutes. The effect of metal ions (60 mM) Mn2+ served asactivator, while EDTA, K+, Mg2+, Cu2+, Fe2+, Zn2+, and Na+acted as inhibitors. The chitinase demonstrated loweraffinity to chitin substrate as indicated by high Km value of0.266 mg/l and a Vmax of 0.067 mg/l sec. Based on SDS-PAGE,chitinase from B. bassiana isolate BB200109 had molecularweight of 60.25 kDa. The study implied the potency ofB. bassiana isolate BB200109 as extracellular chitinaseproducer with its enzyme charateristics seems to bedeveloped as an insect biocontrol agent.